Screening and Characterization of Luminescent Bacterial Strain - Uzma Badar; Erum Shoeb; Komal Daredia; Durr-e-Shawar; Jameela Akhtar; Maqsood A. Ansari (Journal of Basic & Applied Sciences, 2012)
Several samples of sea water and sea organisms were collected for the isolation of luminescent bacterial strain. The samples were collected from Clifton, Hawksbay, fisheri at Landhi and Jeti at Korangi, Karachi, Pakistan, the sea organisms such as Crab, Prawn, Fish, Eel, Fish Gut, Electric Fish were collected. Three different media were used for enrichment of samples that is BOSS, Luminescent Agar (LA) and nutrient broth. A total of twenty one different bacterial strains were selected for further studies on the basis of different colonial morphologies. They were designated as DGU101 to DGU116, DGU221-DGU224 and DGU227. These strains were checked for luminescent and tolerance against antibiotics and heavy metal salts. Only one strain isolated from sea water (Clifton beach) designated as DGU227 showed luminescent on Luminescent Agar (LA) medium. It also exhibited multiple metal and antibiotic resistances. The two large plasmids were isolated from DGU227 which were more than 10 kb in size. The luminescence, growth, quorum sensing phenomenon of bioluminescent bacteria is affected by the presence of metal and antibiotics in environment, which act as inducer, and substrate in activating and enhancing these natural activities. Mostly Luminescent was observed after 24 hours of incubation it enhanced while growing in presence of antibiotic Ampicillin. The strain DGU227 was further identified by 16S rRNA gene analysis and exhibited 98% homology with Vibrio chigassi bacterial strain.